Peningkatan Kualitas Pendidikan melalui Profesionalisme Guru dan Implementasi Manajemen Berbasis Sekolah Meningkatkan Aktifitas Pembelajaran IPA Semester Juli-Desember 2013 Melalui Penerapan Metode CIRC - Asmawarni Asmawarni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
This study aimed to describe the increase in the activities of students learning using learning model Integrated Reading Cooperatif Comprehention (CIRC), which was held on science teaching in the classroom SMPN 4 Lubuk Alung VIII.3.This research is a classroom action research (PTK) implemented two cycles. This study seeks to describe the increased activity of student learning through learning model CIRC on science teaching in the classroom SMPN 4 Lubuk Alung VIII.3. Research procedure has four stages, including planning, implementation, observation and reflection, both in the first cycle and the second cycle. In each cycle the action carried out three times or three times the learning process. Retrieving data using the format of observation. Data were analyzed by percentage formula. The results of the study include: 1) An increase in the activity of students in all aspects compared to the results of initial observations prior learning is done. 2) The highest increase student learning activities in the first cycle of three times the learning happens on the aspect of students' reading and refute the lowest activity. 3) increased activities for students at the second cycle is highest in the concluding activity while the activity is lowest at refute activity. 4) Activity student learning beyond the target achievement for all aspects of learning activities occur in third in the second cycle. 5) The hypothesis about the activities of student learning can be enhanced by the use of CIRC on science teaching methods in the classroom VIII.3 SMP N 4 Lubuk Alung.